First determination of the Planck constant using the LNE watt balance. (1st April 2015) - Thomas, M; Espel, P; Ziane, D; Pinot, P; Juncar, P; Pereira Dos Santos, F; Merlet, S; Piquemal, F; Genevès, G
Abstract: After separate developments of the different elements with continuous characterizations and improvements, the LNE watt balance has been assembled. This paper describes the system in detail and gives its first measurements of the Planck's constant h . The value determined in air is h = 6.626 068 8(20) × 10 −34 Js which differs in relative terms by −0.05  ×  10 −7 from the h 90 value and by −1.1  ×  10 −7 from that of the 2010 CODATA adjustment of h . The relative standard uncertainty associated is 3.1  ×  10 −7 .